Hierarchically Porous Carbons Derived from Metal–Organic Framework/Chitosan Composites for High‐Performance Supercapacitors. Issue 20 (14th May 2019) - Zhong, Shan; Kitta, Mitsunori; Xu, Qiang
Abstract: Hierarchically porous carbon materials with high surface areas are promising candidates for energy storage and conversion. Herein, the facile synthesis of hierarchically porous carbons through the calcination of metal–organic framework (MOF)/chitosan composites is reported. The effects of the chitosan (CS) additive on the pore structure of the resultant carbons are discussed. The corresponding MOF/chitosan precursors could be readily converted into hierarchically porous carbons (NPC‐ V, V= 1, 2, 4, and 6) with much higher ratios of meso‐/macropore volume to micropore volume ( V meso‐macro / V micro ). The derived carbon NPC‐2 with the high ratio of V meso‐macro / V micro =1.47 demonstrates a high specific surface area of 2375 m 2  g −1, and a high pore volume of 2.49 cm 3  g −1, as well as a high graphitization degree, in comparison to its counterpart (NPC) without chitosan addition. These excellent features are favorable for rapid ion diffusion/transport, endowing NPC‐2 with enhanced electrochemical behavior as supercapacitor electrodes in a symmetric electrode system, corresponding to a high specific capacitance of 199.9 F g −1 in the aqueous electrolyte and good rate capability. Good cycling stability is also observed after 10 000 cycles. Abstract : In the hierarchy : A supercapacitor is an electrochemical device with high power density. This article reports a hierarchically porous carbon with a high meso‐/micropore ratio and a high surface area derived from a MOF‐5/chitosan composite, which displays excellent capacitive behavior.